FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING - Soemaryono Soemaryono (CV. Denasya Smart Publisher, 2025)
This research delves into how the size of a public accounting firm, the time it takes to complete an audit, whether a company is publicly owned, and its financial health, or distress, affect whether or not a company changes auditors. The main goal here is to look at the practical impacts of these things – the firm's size, how long audits take (audit delay), if the company is public, and its financial standing – on companies in the manufacturing sector switching their auditors. This study looked at a group of 37 businesses. To test the ideas, the researchers used t-tests and F-tests. The findings show that there's a noticeable link between the size of the accounting firm and how likely a company is to switch auditors. But, other things like audit delay, whether the company is public, and any financial distress didn't seem to have a big effect on auditor switching.